Hemodynamic maladaptation of a pregnant woman as an early marker of preeclampsia - E. V. Timokhina; I. V. Ignatko; I. S. Grigoryan; I. A. Fedyunina; I. M. Bogomazova (Акушерство, гинекология и репродукция)
Prediction of a risk group and early diagnostics of preeclampsia (PE) are crucial for a comprehensive follow-up of women to improve maternal and fetal outcomes. This review presents current data regarding PE prognosis. We have substantially progressed in understanding PE pathogenesis and in the field of angiogenic markers, but not a single test meets the criteria to serve as an optimal biomarker. It has been increasingly emphasized that the role of maternal hemodynamics may be important in predicting PE risk. The cerebral and ophthalmic arteries, blood volume, potential echocardiographic markers to predict PE as well as a marker of heart failure, brain natriuretic peptide (BNP), are actively investigated. The analysis summarizes the data on contemporary markers for PE prognosis by focusing on impaired pregnancy-related maternal cardiovascular adaptation. Assessing hemodynamics represents a potential prognostic marker for impaired maternal cardiovascular adaptation.